Development of the Discovery With Team Assisted Individualization (DTAI) Model to Empower Analytical Thinking Ability in the Material Human Reproductive System - Novitasari, Aulia Setia; Sutarno, Sutarno; Masykuri, Mohammad (UIN Fatmawati Sukarno Bengkulu, 2020)
The objectives of this research and development are: to find out the characteristics of the Discovery with Team Assisted Individualization (D-TAI) learning model, determine the feasibility of the D-TAI learning model, and test the effectiveness of the product model in empowering analytical thinking skills. Model development research refers to Borg & Gall, which was adapted into nine stages: research and data collection, planning, initial product development, initial testing, product revision I, main field revision, product revision II, operational field revision, and final product revision . Analysis of the data used is a qualitative and quantitative descriptive analysis using the Mann Whitney U test. The results of the research and development show: the development of the D-TAI model was carried out with regard to the characteristics of the model. the results of the development of the D-TAI model are applied to the material of the human reproductive system. D-TAI model is able to empower students' analytical thinking skills. The results of the study show a significant difference between the value of analytical thinking skills in the D-TAI model class and the control class that is the average value of the D-TAI model class (74.79) higher than the control class ( 55.91) control with sig level 0.00 <0.05.